2019
DOI: 10.1016/j.jpaa.2018.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Presentations for rook partition monoids and algebras and their singular ideals

Abstract: We obtain several presentations by generators and relations for the rook partition monoids and algebras, as well as their singular ideals. Among other results, we also calculate the minimal sizes of generating sets (some of our presentations use such minimal-size generating sets), and show that the singular part of the rook partition monoid is generated by its idempotents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 67 publications
(117 reference statements)
0
4
0
Order By: Relevance
“…The rook partition monoid, denoted RP X , is a diagram monoid containing P X . It has been studied in a number of settings, and under a variety of different names; see for example [22,42,43,67,68].…”
Section: Rook Partition Monoidsmentioning
confidence: 99%
“…The rook partition monoid, denoted RP X , is a diagram monoid containing P X . It has been studied in a number of settings, and under a variety of different names; see for example [22,42,43,67,68].…”
Section: Rook Partition Monoidsmentioning
confidence: 99%
“…The original study of cellular semigroup algebras may be found in [35]; see also [73,74,112,113] for some recent developments. Another example of how the study of these semigroups can give information about the associated algebras may be found in work of the first author [36], who gives presentations for the partition monoid and shows how these presentations give rise to presentations for the partition algebra; see also [37,43,44]. A further example is given in the paper [27] where idempotents in the partition, Brauer and partial Brauer monoids are described and enumerated, and then the results are applied to determine the number of idempotent basis elements in the finite dimensional partition, Brauer and partial Brauer algebras; see also [28].…”
Section: Introductionmentioning
confidence: 99%
“…It would be interesting to attempt to apply the methods of this paper to other natural diagram categories, such as rook partition categories; cf. [35,54].…”
Section: Partial Brauer Categoriesmentioning
confidence: 99%